Kredibilitas dan Akurasi Pemberitaan Jurnalisme Warga: Analisis Isi Akun X @merapi_uncover pada Maret 2025 - Arya Syaifudin; Suciati (Jurnal Riset Jurnalistik dan Media Digital, 2026)
Abstract. This study analyzes the accuracy and credibility of the citizen journalism account @merapi_uncover on X during March 2025 because its information may affect public safety. This quantitative study employed content analysis of 1,139 posts concerning social events and matters of public interest in Yogyakarta. The assessment covered source attribution, use of official sources, consistency between headlines and photographs/videos, language neutrality, and completeness of the 5W+1H elements. Each indicator was scored 1 or 0, followed by frequency and percentage calculations. The results show that “not attacking particular groups” obtained the highest percentage (34.59%), followed by “consistency between headlines and photographs/videos” (27.30%), “source attribution” (26.60%), “completeness of the 5W+1H elements” (9.65%), and “use of official sources” (1.84%). The @merapi_uncover account maintained language neutrality but remained weak in information verification and completeness. These findings confirm that neutrality does not guarantee accuracy without official sources and complete information and are expected to promote responsible citizen journalism and improve public digital literacy. Abstrak. Kajian ini menganalisis akurasi dan kredibilitas akun jurnalisme warga @merapi_uncover di platform X selama Maret 2025 karena informasinya berpotensi memengaruhi keselamatan publik. Penelitian kuantitatif ini menggunakan analisis isi terhadap 1.139 unggahan mengenai peristiwa sosial dan publik di Yogyakarta. Penilaian meliputi pencantuman sumber, penggunaan sumber resmi, kesesuaian judul dengan foto/video, netralitas bahasa, dan kelengkapan 5W+1H. Setiap indikator diberi skor 1 atau 0, kemudian dihitung frekuensi dan persentasenya. Hasil menunjukkan bahwa indikator “tidak menyerang kelompok” memperoleh persentase tertinggi (34,59%), diikuti “judul sesuai foto/video” (27,30%), “mencantumkan sumber” (26,60%), “kelengkapan 5W+1H” (9,65%), dan “sumber resmi” (1,84%). Akun @merapi_uncover menjaga netralitas bahasa, tetapi lemah dalam verifikasi dan kelengkapan informasi. Temuan ini menegaskan bahwa netralitas belum menjamin akurasi tanpa sumber resmi dan data lengkap serta diharapkan mendorong jurnalisme warga yang bertanggung jawab dan meningkatkan literasi digital masyarakat.